Innovations in cardiac surgery: techniques and applications of 3D printing. Issue 4 (12th November 2018) - Wang, Judy; Coles-Black, Jasamine; Matalanis, George; Chuen, Jason
Aim: The 3D printing is a developing technology which has begun to flourish in fields where the ability to visualize complex anatomy in novel ways can aid interventions. This paper reviews the literature on 3D printing in cardiac surgery.Methods: We performed a literature search in three databases using appropriate search terms to capture publications pertaining to 3D printing in cardiac surgery.Results: Our search demonstrated a paucity of literature in this area, with 27 relevant publications identified since 1980. The majority of articles pertained to the utility of 3D printing in presurgical planning, but its application in other areas was largely unexplored.Conclusion: There is enormous potential for growth of 3D printing in cardiac surgery, which can drastically change the way, we practice medicine.